THE CORRELATION BETWEEN STUDENTS' SELF-EFFICACY AND THEIR ACHIEVEMENT IN LEARNING SCIENCE IN DIFFERENT SCHOOL SYSTEMS - Rena Siti Hasanah, - (2020)
Based on PISA 2018 result, the science achievement of Indonesian students was below average. Students' achievement in learning science influenced by some factors. Such as motivation, emotion regulation, self-efficacy, and school system. This study investigates students' self-efficacy in learning science in different school systems. The present investigation aimed to discover the level of self-efficacy that students in public and private schools belong to. By looking at students' self-efficacy levels, this study tried to find out its correlation with science achievement. There were 170 students from three different public schools and 107 students from three different private schools in Bandung City that involves in this study. This study employed the quantitative research approach, descriptive method, and a correlational research design. The correlation analysis between students' self-efficacy and their achievement in learning science was done in each school. Thus, Spearman-rank correlational analysis was used to investigate the correlation between students' self-efficacy and their achievement in learning science in three public schools and two private schools. For the other one private school used Person correlational analysis. This study shows that students' self-efficacy in both public and private schools was in the medium levels. There were 78.8% of public school students and 76.6% of private school students classified at the medium level. However, there was no correlation between students' self-efficacy and their achievement in learning science both in public and private schools.